Non-communicable Disease Risk Factors and Healthcare Worker’s Perspective on Tackling Them amongst Tribal Population: A Mixed Method Study - Cowshik Esswaran; M. Vijayalakshmi; M. Jannath Hameeda Banu (Preventive Medicine: Research & Reviews)
Introduction: Early epidemiologic transition and increase in the incidence of non-communicable diseases (NCDs) are observed amongst tribal population. The objectives of this study were to assess the prevalence of NCD Risk factors and to document the challenges faced by healthcare providers. Methodology: A mixed method study was conducted in a Tribal area of Udumalpet, Tamil Nadu. A community-based cross-sectional study amongst 362 adults of Muduvar tribes using the WHO STEPwise approach for the surveillance was done. In-depth interviews were conducted, and thematic analysis was done using WEFT-QDA software. Results: The mean age of study participants was 43.51 years. The mean age of initiation of tobacco was 19.66 years. Half had consumed alcohol at least once. The behavioural risk factors were associated with male sex, increase in age, marital status, education and employment. Qualitative analysis showed that healthcare providers faced challenges in health system and community levels. Conclusions: There is an increased prevalence of behavioural risk factors of NCDs amongst the Muduvar tribes in Tiruppur. The challenges faced by healthcare providers support the need for a WHO PEN package at every level.